Quantitative nursing research - Knapp, Thomas R. (Sage Publications, 1998)
You may stop looking now. Quantitative Nursing Research is the answer to the prayers of graduate students and practitioners who have sought the key to this often intimidating subject. In this highly readable (dare we say enjoyable?) work, Thomas R. Knapp guides the reader through the basic definitions, fundamentals of design, and techniques of quantitative research.